New Insights into the Mechanical Properties, Functional Fatigue, and Structural Fatigue of Ni-Ti Alloy Porous Structures - Dianyu Tang; Yong Hu; Lei Yang (Metals, 2023)
Ni-Ti shape memory alloys (SMAs) are widely noticed and have captured great interest due to their unique shape memory effect and super elasticity. Porous Ni-Ti SMAs have the typical characteristics of both porous metals as well as shape memory alloys. Because of the uneven stress distribution, cyclic loading has a more significant effect on the phase transformation and plastic deformation of Ni-Ti porous compared with Ni-Ti bulk. This paper overviews the structural and functional fatigue experiments and numerical simulation progress of Ni-Ti porous. The factors affecting the fatigue performance of the Ni-Ti lattice structure and the methods for enhancing its fatigue performance are elaborated. More importantly, the point of the coupling analysis of structural fatigue performance and functional fatigue performance is proposed for the study of porous Ni-Ti shape memory alloys.